Mechanical and micromechanical properties of alkali activated fly-ash cement based on nano-indentation. (15th March 2016) - Lee, Hyuk; Vimonsatit, Vanissorn; Chindaprasirt, Prinya
Highlights: Mix design using Taguchi's method was presented to determine critical factors. Silica fume has the most adverse impact on the compressive strength. Using deconvolution technique confirms four phases of reaction products. High strength is achieved N-A-S-H phase greater than 40% of total volume fraction. Activation degree is recommended to be 60% to achieve high strength mixture. Abstract: This paper presents mechanical and micromechanical properties of alkali activated fly-ash cement (AAFA) based on statistical analysis with nano-indentation test. Mix proportions of AAFA are designed using Taguchi's approach. Four variables viz, silica fume (SF), sand to cementitious material ratio (s/c), liquid to solid ratio (l/s) and superplasticiser (SP) content were the parameters tested. Indentation elastic modulus, hardness and packing density are studied. The results show that the increase in sand has the greatest contribution to the increase in density. For compressive strength, normal paste without SF, sand and SP with l/s of 0.6 gives the highest strength and the increase in SF significantly contributes to the adverse effect on compressive strength. For the indentation data, the analysis using deconvolution technique confirms the four phases of reaction products of AAFA. The main phase is sodium aluminosilicate hydrate (N-A-S-H), which is over 40% of the volume fraction. The microporomechanics of AAFA paste and mortar also demonstrate the relationships between the N-A-S-H volume fraction and strength; and activation degree and strength.